P018 Protease activated receptor 2 (PAR2) expression in the myeloid compartment impacts osteoclastogenesis. (21st February 2018) - McGrath, S; Hultin, L; Lockhart, JC; Goodyear, CS
Abstract : Introduction: Protease activated receptor 2 (PAR2) is a G protein coupled receptor responsive to serine proteases, which plays a key role in inflammation and pain reception. Rheumatoid arthritis (RA) patients have up-regulated surface expression of PAR2 in circulating monocytes which correlates with disease activity. We have previously demonstrated that Par2 -/- mice are protected from inflammation, bone erosion, and cartilage destruction in a Freund's Complete Adjuvant (FCA) induced arthritis model. However, it is unclear how PAR2 affects the composition of the myeloid compartment and osteoclastogenesis. Objectives: The aim of this study was to evaluate the impact of loss of PAR2 on the myeloid compartment and osteoclastogenesis. Methods: Bone marrow (BM) from 6–10 week old Par2 -/- and control C57BL/6 mice was cultured in pro-osteoclastogenic media for 5 days and the generated mature osteoclasts, tartrate-resistant acid phosphatase positive (TRAP) multinucleated cells, were counted. The resorption potential of these cells was assessed using osteolysis plates and the total osteo-resorption quantified after 7–14 days of culture. BM was also collected for flow cytometric analysis of the haematopoietic cellular composition (with the following markers: CD3, B220, CD11b, Ly6C, Ly6G, CD115, and CD117) and assessed for osteoclast precursors. Results: In vitro osteoclastogenesis revealed an increase in numbers of mature osteoclasts from Par2 -/- BM compared to WT, corresponding with increased levels of resorption. Flow cytometry of BM from both WT and Par2 -/- mice showed 3 distinct monocyte populations defined by the cell surface expression levels of CD11b and Ly6C. The overall ratio of these populations was not altered in Par2 -/- animals. Conclusions: BM from Par2 -/- mice has increased osteoclastogenic potential and overall resorptive activity. We propose that this is not due to differences in bone marrow residing osteoclast pre-cursor numbers. This study indicates a potential role for PAR2 in osteoclast differentiation and bone remodelling. Acknowledgements: The research was funded by Medical Research Scotland (MRS) and supported by Astrazeneca. Disclosure of interest: S. McGrath: None declared, L. Hultin Employee of: Astrazeneca, J. Lockhart: None declared, C. Goodyear Consultant for: AstraZeneca